The moth diaries - Klein, Rachel, 1953- (London : Faber and Faber, 2005)
A sixteen-year-old girl at an exclusive girls' boarding school during the late sixties uses the pages of her journal to try and come to terms with the dark forces that seem to rule her life.
Adult.
Adult
Keywords: Boarding schools -- Fiction; Diaries -- Authorship -- Fiction; Teenage girls -- Fiction; Diaries -- Technique -- Fiction; Girls -- Fiction; Gothic novels; Private schools -- Fiction; Psychological fiction; Teenagers -- Fiction